2018
DOI: 10.1007/s11270-018-3752-y
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Zooplankton Behavior Caused by a Mixture of Pesticides

Abstract: Behavioral changes have been considered as appropriate to evaluate sublethal effects of pollutants. The aim of this study was to evaluate the effects of a mixture of pesticides, with glyphosate and 2,4-D (Gly + 2,4-D) as active ingredients, on the zooplankton evasion behavior from the fish Cnesterodon decemmaculatus. An increase in the evasion behavior was observed for copepods at two different concentrations of the Gly + 2,4-D mixture, for cladocerans at the lowest pesticide concentration, and for rotifers at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Recent studies have demonstrated that glyphosate has negative effects on ecosystems and humans. It provokes severe effects to many non-targeted organisms, with for instance effects on reproduction in soil invertebrates, changes in the zooplankton behavior, reduction of fertility in some fishes [16,17]. Furthermore, anxiety and depression have been observed for mice following chronic exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that glyphosate has negative effects on ecosystems and humans. It provokes severe effects to many non-targeted organisms, with for instance effects on reproduction in soil invertebrates, changes in the zooplankton behavior, reduction of fertility in some fishes [16,17]. Furthermore, anxiety and depression have been observed for mice following chronic exposure.…”
Section: Introductionmentioning
confidence: 99%